Effect of biogas sludge meal supplement in feed on growth performance molting period and production cost of giant freshwater prawn culture. (August 2022) - Whangchai, Niwooti; Yaibouathong, Daovieng; Junluthin, Pattranan; Balakrishnan, Deepanraj; Unpaprom, Yuwalee; Ramaraj, Rameshprabu; Pimpimol, Tipsukhon
Abstract: The worldwide prawn industry strives for better production and environmental sustainability. Shrimp feed is one of the most expensive aquaculture inputs; therefore, it must be cost-effective and environmentally safe. Fish meals in aquaculture are becoming unsustainable due to the cost and environmental concerns. The effects of a biogas sludge meal supplement in feed on freshwater prawn productivity were studied. This study aimed to examine the growth, survival rate, yield, feed conversion ratio, and molting period of giant freshwater prawns (Macrobrachium rosenbergii) fed with and without biogas sludge a low-cost resource. The four treatments were T1 (0% biogas sludge), T2 (10% biogas sludge), T3 (20% biogas sludge), and T4 (30% biogas sludge). Protein content ranged from 26.7 to 27.4% in the experimental diets. The experiment was conducted in 3 × 3x1.5 m cages in an earthen pond for 80 days. The data shows that freshwater prawn growth performance did not differ significantly across treatments (P > 0.05). Biogas sludge has been demonstrated to be a low-cost feed component for freshwater prawns. Regarding survival, productivity, and feed conversion ratio, T2 (10% biogas sludge) outperformed the other two. As a result of the research, it was determined that 10% of biogas sludge might be used as a low-cost freshwater prawn feed option. The molting period of freshwater prawns fed biogas-containing feed was investigated at various levels. Freshwater prawns grown in baskets in a pond at 32.2 °C for a trial period of 90 days were molted differently (P > 0.05). The molting periods for Tl, T2, T3, and T4 were 19, 18, 19.8, and 20.8, respectively. In addition, the research suggests efficient and long-term methods for supplying nutrient-dense prawn feed to aquaculture production systems. Graphical abstract: Image 1 Highlights: The investigation was conducted on samples collected biogas waste sludge for prawn feed. Biogas waste sludge is a suitable ingredient for prawn feed formulation. Biogas waste sludge nutrient concentrations and prawn farming by waste to wealth aspects. Biogas waste sludge can be used to make cheap and nutritious fish feed.